Basidiomycota Fungi and ROS: Genomic Perspective on Key Enzymes Involved in Generation and Mitigation of Reactive Oxygen Species - Mattila, Hans; Österman-Udd, Janina; Mali, Tuulia; Lundell, Taina (Frontiers in Fungal Biology, 2022)
Our review includes a genomic survey of a multitude of reactive oxygen species (ROS) related intra- and extracellular enzymes and proteins among fungi of Basidiomycota, following their taxonomic classification within the systematic classes and orders, and focusing on different fungal lifestyles (saprobic, symbiotic, pathogenic). Intra- and extracellular ROS involved enzymes (49 different protein families, summing 4170 protein models) were searched as protein encoding genes among 63 genomes selected according to current taxonomy. Extracellular and intracellular ROS-involving metabolism and mechanisms in Basidiomycota are illustrated in detail. In brief, it may be concluded that differences between the set of extracellular enzymes activated by ROS, especially by H2O2, and involved in generation of H2O2, follow the differences in fungal lifestyles. The wood and plant biomass degrading white-rot fungi and the litter-decomposing species of Agaricomycetes contain the highest counts for genes encoding various extracellular peroxidases, mono- and peroxygenases, and oxidases. These findings further confirm the necessity of the multigene families of various extracellular oxidoreductases for efficient and complete degradation of wood lignocelluloses by fungi. High variations in the sizes of the extracellular ROS-involved gene families were found, however, among species with mycorrhizal symbiotic lifestyle. In addition, there are some differences among the sets of intracellular thiol-mediation involving proteins, and existence of enzyme mechanisms for quenching of intracellular H2O2 and ROS. In animal- and plant-pathogenic species, extracellular ROS enzymes are absent or rare. In these fungi, intracellular peroxidases are seemingly in minor role than in the independent saprobic, filamentous species of Basidiomycota. Noteworthy is that our genomic survey and review of the literature point to that there are differences both in generation of extracellular ROS as well as in mechanisms of response to oxidative stress and mitigation of ROS between fungi of Basidiomycota and Ascomycota.